Cases and materials on environment and pollution laws - "Lal, C. S" (Allahabad, 2003)
This small hand book is designed to serve as a ready reckoner for all concerned with the subject, including the Environmental Practitioners, providing direct access to all the important Acts & Rules affiliated with the subject of Environmental & Pollution Acts & Rules that are all amended up to date including some latest case laws of the Supreme Court & High Court. This is a most impressive compilation/well referenced hand book, which the readers Industries/Environmentalists/ Bench & Bar and Public at large would turn to a definite source of reference on the subject.
Keywords: Environmental law and legislation